Costly communication and learning from failure in organizational coordination - Fehr, Dietmar (European economic review, 2017)
This paper investigates the coordination failure that arises from combining two small pre-existing groups and focuses on the reaction of group members to this change in environment. In an experiment, small groups were first able to establish a coordination history in a repeated minimum-effort game; in the second phase, two groups with different histories were combined into a larger group. Unlike most of the previous literature, subjects could endogenously choose to communicate in the newly formed group for a small fee. While communication proved to be necessary for preventing coordination failure in the newly formed group, only every second subject was willing to implement communication. Particularly, subjects from groups with a less efficient coordination experience in the first phase were more likely to realize the potential of coordination failure in the new group and were thus more likely to decide for communication. The results may be useful for understanding how groups coordinate in changing environments as they are common in economic contexts.